Abordaje de enfermería en mujeres con lupus eritematoso sistémico - Aguilar Balseca, Joane Nicole (2022)
ABSTRACT: Systemic Lupus Erythematosus (SLE) is a chronic, progressive, multisystemic disease with a high incidence. Hence, the World Health Organization defines SLE as a disease of the immune system that mistakenly damages healthy tissue that can affect any body part. Lupus patients have a negative impact on physical and mental health, with fatigue, pain, and depression being the main determinants of quality of life, which makes it necessary for them to receive comprehensive and holistic care. The general objective was to determine Callista Roy's theory in the care of patients with systemic lupus erythematosus through a bibliographic review; The specific objectives were: To analyze the nursing intervention considering the four adaptive modes of Callista Roy's theory in the care for patients with systemic lupus erythematosus and to define the leading nursing diagnostic labels based on the NANDA taxonomy, to improve their health condition. Health. One thousand one hundred sixty-nine scientific articles from different databases were reviewed. By applying inclusion and exclusion criteria, a sample of all 44 bibliographic sources was reached, of which 27 were used for the triangulation process. Based on the results, the nursing approach was determined using Callista Roy's theory and its four modes: physiological mode, self-concept, role function mode, and interdependence mode, guaranteeing the establishment of adaptive responses in a disease situation. Nursing interventions enable the patient to be in balance with himself and his environment, thus improving the health and quality of life of these patients with autoimmune diseases. Diagnostic labels were proposed that could occur in this type of patient, such as acute pain, chronic pain, impaired physical mobility, impaired skin integrity, situational low self-esteem, anxiety, discomfort, fear, hopelessness, ineffective role performance, body image disorder, interruption of family processes, social isolation. Keywords: Systemic lupus erythematosus, nursing approach, adaptation, Callista Roy